Inhibiting insulin resistance mechanisms by DTS phytocompound: an experimental study on metabolic syndrome-prone adipocytes - Catanzaro, R.; Lorenzetti, A.; Allegri, et al., F. (Acta Biomedica Atenei Parmensis, 2012)
The present study was designed to determine whether DTS a phytocompound endowed with antioxidant properties, could beneficially modulate nitric oxide (NO) production stimulated by lipopolysaccharide (LPS) and tumor necrosis factor-α (TNF-α) in adipocytes. Combined stimulation (CS-treatment) exerted by using 5 μg/ml of LPS together with 100 ng/ml of TNF-α significantly enhanced NO production in 3T3-L1 adipocytes. Preincubation of the adipocytes with DTS (10-30 mM) inhibited such phenomenon in a dose-dependent fashion. The production of NO was decreased by 52% at the concentration of 30mM of DTS. The decrease in NO production by DTS was associated also with a decrease in inducible nitric oxide synthase (iNOS) protein and iNOS mRNA expression. Nuclear factor-kappa B (NF-κB) was significantly enhanced by CS-treatment, while the pretreatment with 30 mM of DTS prevented the activity by 27%. IL-6 production in 3T3-L1 adipocytes was markedly increased by CS stimulus, and the enhanced secretion of IL-6 was suppressed in a dose-dependent manner by DTS. These results suggest that DTS regulates iNOS expression and NO production in adipocytes through the modulating activation of NF-κB and may have a potential clinical application within protocols designed for treating metabolic syndrome.